Analyze of House Conditions and The Rat Existence Affected to The Leptospirosis Cases in Klaten District - Nisa Azza Katulistiwa; Kusuma Scorpia Lestari (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract: In Klaten district,  leptospirosis cases raised  up  during  6 years (2006–2013), except in 2012.  The  healthy houses coverage raised up as well, although some houses still had not met healthy house criteria. The aim of this study was to analyze of house conditions and the rat exsistence affected to the leptospirosis cases in Klaten district. This study was observational analytic study used case control design. This study  was conducted on November, 2013–June, 2014 by using questionnaire, interview, and observation. The sample was 60 respondents with 30 cases and 30 controls. The independent variables  were the house conditions, house components, sanitation facilities, behavior,  and rat existence in the  house. Bivariate analysis  used chi square  test,  the  result showed that the  house conditions (p value  =  0.009 OR = 6.882), behavior  (p value = 0.017 OR = 6.000), and the rat existence in the house (p value = 0.030 OR = 10.545) were related to the leptospirosis cases. Multivariate analysis  used logistic regression test, the result showed unhealthy house conditions was the dominant risk factors that affect to the leptospirosis cases with value of probability about 74,6% and  two-fold  higher  risk compared with healthy house conditions. The suggestion for community in Klaten District is attempting to improve  the environmental house health by having a clean  and healthy living, such as always to put the garbage away to the waterproof  and closed bins and to put the garbage away regularly from house in the evening to prevent  rats go into house.Keywords: housing conditions, rat, unhealthy houses, leptospirosis